The Causes of Drug Addiction among Addicts undergoing Treatment at the National Center for Rehabilitation of Addicts - Addob Al-Zaben, Ghadeer Barnas (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aims to identify the causes of drug addiction in the National Center for the Rehabilitation of Addicts. The researcher employed the social survey method. The study sample consisted of 40 inmates residing in the National Center for Rehabilitation of Addicts, who were randomly selected by 72% of the inmates. For the purposes of the study, the researcher used the questionnaire, which consisted of two parts. The first includes demographic, social and economic data, whereas the second consists of 37 words distributed on three different dimensions: social, psychological, and economic. The descriptive statistics (percentages), the T.test, and the one way ANOVA test were used. The study showed the following results: of the most important social causes of drug addiction are bad companions and weak family control, and the psychological causes include stress, anxiety, and curiosity, among others. In addition, it has been found that the economic reasons involve the affordability of drugs. The study has showed that there is no statistically significant difference (0≤.05) in the causes of drug abuse according to educational level variables and the social status. هدفت الدراسة معرفة الأسباب المؤدية إلى إدمان المخدرات لدى المدمنين الذكور الخاضعين للعلاج في المركز الوطني لتأهيل المدمنين في الأردن، وقد اتبعت الباحثة منهج المسح الاجتماعي ،تكونت عينة الدراسة من (40)من النزلاء المقيميين في المركز الوطني لتأهيل المدمنين ،تم اختيارهم بطريقة العينة العشوائية بنسبة(72%)،ولأغراض الدراسة قامت الباحثة باستخدام أداة الاستبانة التي تكونت من جزئيين :الأول ويشتمل على البيانات الديمغرافية والاجتماعية والاقتصادية، والثاني :يتكون من (36)عبارة وزعت على ثلاثة محاور مختلفة (اجتماعية ،نفسية ، واقتصادية)، وتم استخدام الاحصاء الوصفي (النسب المئوية)واختبارات (T.test)و اختبار التباين الاحادي One way ANOVA)). أظهرت الدراسة النتائج الآتية: أن أهم الأسباب الاجتماعية لإدمان المخدرات مرافقة أصدقاء السوء، إضافة إلى ضعف الرقابة الاسرية ،أما أبرز الأسباب النفسية التي يرى المدمنين بأنها قد تدفع إلى إدمان المخدرات ،الشعور بالتوتر، والفضول وحب الاستطلاع ،والشعور بالقلق، كما بينت نتائج الدراسة أن من أبرز الأسباب الاقتصادية التي تدفع إلى إدمان المخدرات، رخص أسعار المواد المخدرة ، وأظهرت الدراسة عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة(0.05)فأقل في الأسباب المؤدية إلى تعاطي المخدرات تبعا لمتغيرات المستوى التعليمي، والحالة الاجتماعية.